264 Damage accrual in swedish systemic lupus erythematosus: secondary sjögrens syndrome is among the factors associated with increased risk. (April 2019) - Frodlund, Martina; Reid, Sarah; Wetterö, Jonas; Dahlström, Örjan; Sjöwall, Christopher; Leonard, Dag
Abstract : Background: Although the expected survival of patients with systemic lupus erythematosus (SLE) has improved during the last 50 years, accrual of damage remains a critical concern. Acquired damage is tightly linked to decreased quality-of-life and premature death, and could be due to raised disease activity, drug-related side-effects or co-morbidities. Methods: Accumulation of organ damage was studied in 543 well-characterized and from 1998 and onwards consecutively recruited prevalent/incident SLE cases meeting the 1982 American College of Rheumatology (ACR82) and/or the 2012 SLICC criteria. The SLICC/ACR damage index (SDI) was used to estimate damage. Disease variables were evaluated regarding association with damage accrual, and time to first damage. Detailed information on clinical and immunological features, as well as damage in each SDI domain, where at hands. Standardized mortality rate was calculated and causes of death recorded. Comparisons between groups were performed using Chi-square- or Mann-Whitney U-tests, p-values<0.05 were considered significant. Results: 59% of the patients had an SDI score 1% and 25% had extensive damage defined as SDI 3. Patients with presence of damage (SDI 1) were significantly older at disease onset, had longer SLE duration and fulfilled further classification criteria. Caucasian ethnicity was more common among cases with damage. Having ACR82-defined neurologic disorder, antiphospholipid syndrome (APS), any antiphospholipid antibody (positive IgG anti-2-GPI or a lupus anticoagulant test, separately) as well as concomitant co-morbidities such as hypertension, hyperlipidemia, diabetes, depression and secondary Sjögrens syndrome were associated with presence of damage (SDI 1). In addition to factors associated with SDI 1, serositis, renal and hematological disorder as well as interstitial lung disease and positive IgG anti-cardiolipin were associated with extensive damage (SDI 3). Time to first damage was significantly shorter for males and for cases with a positive lupus anticoagulant test, whereas APS patients were borderline significant. Cases with malar rash and anti-La/SSB antibodies had significantly longer time to first damage. Malignancy was the most common cause of death. Conclusions: Despite that Swedish health care is tax-funded and offers universal access, a considerable number of patients are affected by irreversible damage over time. We confirm previous observations for several damage associations and report secondary Sjögrens syndrome to be associated with an increased risk of organ damage in SLE. Funding Source(s): This work was supported by grants from the Swedish Rheumatism Association, the County Council of Östergötland, the Swedish Society of Medicine, the King Gustaf Vs 80 year anniversary foundation and the King Gustaf V and Queen Victorias Freemasons foundation.